(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
A mathematical model has been developed for the reaction of m-cresol with indene in the presence of benzenesulphonic acid as a catalyst using Yates pattern experimental design and indanyl m-cresol has been obtained in high yield. Bangladesh J. Sci. Ind. Res. 42(1), 1-8, 2007